Pemberdayaan Masyarakat Dalam Pengelolaan Bank Sampah Desa Salam Kecamatan Wonodadi Kabupaten Blitar - ahmad riza asnawi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
This research is motivated by the existence of several problems, including; waste management that does not pay attention to the environment, public awareness to dispose of waste in its place is still lacking, lack of public knowledge in managing waste and waste is still considered something useless. This study aims to describe the stages and approaches to empowerment in waste bank management carried out at the Salam Village Waste Bank, Wonodadi District, Blitar Regency. The research method used is descriptive qualitative research method, this research uses 3 informants. The sampling technique was carried out using a purposive sampling technique. The results of the study show that community empowerment through the management of the Salam Village waste bank provides benefits for the community, especially women, namely, minimizing the circulation of waste around the environment, and making the environment healthier. The stages of empowerment in the Salam Village waste bank are in accordance with the theory put forward by Isbandi Rukminto Adi, in his book, Social Welfare (Social Work, Social Development and Development Studies), which explains that there are seven stages of empowerment namely, preparation stage, assessment stage, alternative planning stage program, Action Plan Formulation Stage, program implementation stage, monitoring and evaluation stage, and termination stage The approach used in the management of the Salam Village Garbage Bank uses micro intervention Empowerment through waste bank activities can be an alternative in creating an empowerment program Apart from being useful in empowering Community Empowerment through this waste bank activity is also useful for reducing the impact of environmental pollution due to waste. This activity has also succeeded in changing the mindset of the community, especially the customers of the Salam Village waste bank towards waste. Initially, residents only thought that waste was useless and now it must be removed quickly to be wiser in responding to it, local residents can use useless items to become useful and have economic value.